A recombinant DNA and vaccinia virus prime–boost regimen induces potent long-term T-cell responses to HCV in BALB/c mice - Deng, Yao (Vaccine, 2009)
To explore the best prime–boost regimen and evaluate the T-cellular response memory against HCV, we constructed two DNA vaccine candidates (pVRC-CE1E2 and pAAV-CE1E2) and two recombinant viruses (rTTV-E1E2 and rAAV-E1E2) and then assessed the immune response to different prime–boost patterns in BALB/c mice. The rTTV-E1E2 boosted the immune response to HCV DNA vaccine prime significantly, and the inverted terminal repeat sequence harboring DNA construct PAAV-CE1E2 was the best prime agent in this study. Our study provides new information for both the prime–boost regimen and long-term T-cell response for HCV vaccine development.